The Biggest Damned Hat : Tales from Alaska's Territorial Lawyers and Judges - Cravez, Pamela (Book collections on Project MUSE., 2017)
"Alaska history from the days before statehood is rich in stories of colorful characters--prospectors, settlers, heroes, and criminals. And right alongside them were judges and lawyers, working first to establish the rule of law in the territory, then, later, laying the groundwork for statehood. [This book is a] collection of stories ranging from the gold rush to the 1950s. Built on interviews and oral histories from more than fifty lawyers who worked in Alaska before 1959, and buttressed by research into legal history, the book offers a ... portrait of law in the territory--from laying the groundwork for strong civil and criminal law to helping to secure mining and fishing rights to the Alaska Court-Bar fight, which pitted Alaska's community of lawyers against its nascent Supreme Court. Bringing to life a time long past--when some of the best lawyers had little formal legal education--[this book] fills ... a part of the story of Alaska's history."--